Appropriation des nouvelles médiations technopédagogiques. Enjeux, contraintes et perspectives pour une éducation de qualité pour tous en Afrique - Mama Chandini (Éducation et Socialisation)
Africa is facing certain difficulties that compromise the accessibility of educational services. The New techno-pedagogical mediations (NTM), which have emerged as an alternative training method adapted to these emergency educational situations, are therefore challenged by the issues of education in times of crisis, massification, democratization, universalization of education and the management of large groups. However, multiple constraints have been identified that weigh on the process of appropriation of the NTM in Africa. To remedy this, the study shows that the continent has many assets that are favorable to the widespread promotion of this device. All of which augurs promising prospects for the appropriation of the NTM as a tool for educational planning, with a view to achieving the objective of quality education for all in Africa.